Decision-Making Process Regarding Fertility Among Reproductive-Age Women With Cancer in Taiwan. Issue 5 (September 2017) - Huang, Sheng-Miauh; Hsieh, Pei-Ling; Hsiung, Yvonne; Tseng, Ling-Ming; Chen, Ping-Ho; Hung, Chia Tai
Abstract : Background: Previous studies indicate that women with cancer experience infertility after cancer-related treatment. With the rapid progress in fertility science, women face diverse and uncertain choices regarding pregnancy. Objective: The aim of this study is to understand the decision-making process regarding fertility choices among reproductive-age women with cancer in Taiwan. Methods: Grounded theory methodology guided data collection using in-depth interviews with 18 women diagnosed and treated for cancer. Verbatim transcriptions were analyzed using constant comparative analysis and open, axial, and selective coding. Results: The core category that describes the decision-making process regarding fertility among reproductive-age women with cancer is "searching for balance in life and creating value in life." The decision process was divided into 3 phases: needing to have children before treatment, struggling with self-living during cancer treatment, and returning to life after treatment. The style of cancer participants' decision making in pregnancy was divided into 3 patterns: action taking, hesitation, and persistence. Conclusions: Decision making regarding fertility among women with cancer was affected by the need for children before treatment and their experience during treatment. Implications for Practice: Health providers should be aware of and understand the needs of women with cancer to balance their need for children with their perception of their cancer prognosis and its effects on fertility, and help them with pregnancy planning if desired.